Hospital use in Aboriginal and non‐Aboriginal patients with chronic disease. (16th April 2017) - Whyatt, David; Yap, Matthew; Tenneti, Raji; Pearson, Glenn; Vickery, Alistair
Abstract: Objective: The objective of this study was to compare rates of hospital utilisation in Aboriginal and non‐Aboriginal peoples before and after hospital admission for chronic obstructive pulmonary disease, heart failure and/or type 2 diabetes mellitus. Methods: This was a longitudinal cohort study from 2002 to 2014, which was conducted in all hospitals in Western Australia. The participants of this study were Aboriginal and non‐Aboriginal patients with a principal diagnosis of heart failure, type 2 diabetes or chronic obstructive pulmonary disease, on admission to hospital, where such an event had not occurred in the previous 3 years. Inpatient days and ED presentations were the main outcome measures. Results: Among the patients with chronic disease, Aboriginal people have similar inpatient days for all causes compared to non‐Aboriginal people. However, they have much higher ED presentations in comparison. Age of onset of cardinal events occurs 15–20 years earlier in Aboriginal patients with chronic disease. Although age has little influence on ED presentations in non‐Aboriginal chronic disease patients, younger Aboriginal people with chronic disease present far more often to ED than older Aboriginal people. Conclusions: Aboriginal people use health services in a different manner when compared to non‐Aboriginal people. In a subset of patients with chronic disease, high use may be reduced with better access to primary healthcare. Policy‐makers and healthcare providers should examine healthcare use from primary to tertiary care among the Aboriginal population, with a particular focus on ED presentations; investigate the underlying causes driving specific patterns of health service utilisation among Aboriginal people; and develop interventions to reduce potential deleterious impacts, and enhance the potential benefits, of specific patterns of healthcare use.